Interface shear resistance of steel-concrete composite beams using U-bolt shear connectors. (1st July 2023) - Gao, Shan; Bai, Qi; Guo, Lanhui; Kang, Shao-Bo
Highlights: Push-out specimens with assembly straight bolt and U-bolt shear connectors were tested. Longitudinally arranged U-bolts show the largest bearing capacity and initial stiffness. The increase in concrete strength and bolt diameter can improve the performance of U-bolts. The prediction formulas for the performance of U-bolt shear connectors are proposed. Load-slip model of longitudinally arranged U-bolt shear connectors are proposed. Abstract: To improve the interface shear resistance of steel-concrete composite beams, a novel U-shaped bolted shear connector was proposed and tested in a push-out test by considering the influence of bolt type, U-bolt arrangement and dimensions. Based on the validated modeling techniques, a parametric analysis is conducted by considering the influence of concrete strength, bolt diameter and bolt strength. The results show that the failure mode of the specimens with U-bolt is bolt fracture and concrete cracking, whilst that with straight bolts is bolt fracture and local concrete crushing. Compared to the straight bolts with the same embedded height, the bearing capacity and initial stiffness of the longitudinally arranged U-bolts are significantly improved by 48.82% and 51.95% respectively, whilst compared to the U-bolts arranged transversely, the increase in the bearing capacity and the initial stiffness is only 5.10% and 29.90% respectively. The area increase in the concrete tenon inside the longitudinally arranged U-bolt would increase its initial stiffness, rather than the bearing capacity. The ductility coefficient of the U-bolts arranged longitudinally is significantly smaller than that of the straight bolts and transversely arranged U- bolts. The simulated results show that the increase in concrete strength and bolt diameter can significantly improve the bearing capacity and initial stiffness of U-bolts arranged longitudinally, but greatly reduce the corresponding maximum displacement and ductility coefficient. The increase in bolt strength would comprehensively improve the shear performance of U-bolts arranged longitudinally. Based on the tested and simulated results, the prediction formulas for the shear bearing capacity, initial shear stiffness, peak slip and the load-slip model of longitudinally arranged U-bolt shear connectors are proposed.